2022
DOI: 10.1007/s40618-022-01744-3
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin-expressing endothelial progenitor cells and serum osteocalcin forms are independent biomarkers of coronary atherosclerotic disease severity in male and female patients

Abstract: Purpose Osteocalcin (OC), an osteoblast-derived regulator of metabolic processes, and circulating early endothelial progenitor cells (EPC, CD34 − /CD133 + /KDR +) expressing OC (OC +) are potential candidates linking bone metabolism and the vasculature and might be involved in vascular atherosclerotic calcification. This study aimed at assessing the association of circulating levels of different OC forms and of EPCs count with disease severity in patients with documented coronary atherosclerosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Low serum osteocalcin levels are associated with a higher occurrence of T2DM and its complications, as well as a higher rate of all-cause and cardiovascular death in T2DM [31,32]. The CVAI is the best obesity parameter for predicting the prevalence of diabetes and has the strongest relationship with the occurrence rate of CVD in T2DM [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Low serum osteocalcin levels are associated with a higher occurrence of T2DM and its complications, as well as a higher rate of all-cause and cardiovascular death in T2DM [31,32]. The CVAI is the best obesity parameter for predicting the prevalence of diabetes and has the strongest relationship with the occurrence rate of CVD in T2DM [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the assumptions that endothelial progenitor cells expressing OC are able to activate calcification in vitro and in vivo [ 147 ], a cross-sectional study in a cohort with coronary artery atherosclerosis evaluated the role of different OC forms. The study revealed a significant association between the count of circulating early endothelial progenitor cells expressing OC, coronary atherosclerosis severity and CV risk factors such as total cholesterol (TC), LDL-C, and TG.…”
Section: Osteocalcinmentioning
confidence: 99%
“…Association between osteocalcin and CVAI and ASCVD risk serum osteocalcin levels are associated with a higher occurrence of T2DM and its complications, as well as a higher rate of all-cause and cardiovascular death in T2DM [31,32]. The CVAI is the best obesity parameter for predicting the prevalence of diabetes and has the strongest relationship with the occurrence rate of CVD in T2DM [8,33].…”
Section: Association Between General Characteristics and Osteocalcin ...mentioning
confidence: 99%